Michael Löwy: marxismo e crítica da modernidade - Resenha - Py, Fábio (Horizonte, 2016)
QUERIDO, Fábio Mascaro. Michael Löwy: marxismo e crítica da modernidade. São Paulo: Boitempo; Fapesp, 2016. 199p. ISBN 978-85-7559-483-4